1000 Questions and Answers - Kerrod, Robin (London Kingfisher Publications Plc, 2002)
What's the difference between a star and a planet? What killed the dinosaurs? What is acid rain? Who built the first cities?$1 (Ba host of straight-to-the-point, and equally eccentric questions that kids love to ask are covered in this amazing compendium. 1000 Questions and Answers combines eight fascinating subjects: Stars and Planets, Planet Earth, Dinosaurs, Birds, Ancient Civilizations, Knights and Castles, Inventions and Transportation, in one fully indexed volume.s
Keywords: General Knowledge